Outcomes after liposuction-based treatment of lymphedema: a systematic review and meta-analysis - Chen, Junzhe; Feng, Xiyao; Zhou, Yan; Wang, Yun; Xiao, Shune; Deng, Chengliang (Frontiers in Oncology, 2025)
BackgroundLymphedema, a chronic condition involving lymphatic fluid accumulation, affects over 250 million people worldwide. Liposuction (LS), introduced in 1989, offers a minimally invasive option for non-pitting lymphedema by reducing fibrotic and hypertrophic tissues. However, LS requires ongoing compression therapy as it does not address the underlying lymphatic dysfunction. Although integrated approaches combining LS with lymphovenous anastomosis (LVA) or vascularized lymph node transfer (VLNT) aim to address both fluid removal and lymphatic repair, there remains a lack of consensus regarding the efficacy of these integrated liposuction-based treatments.MethodsA systematic review and meta-analysis conducted by the PRISMA and AMSTAR guidelines included studies from 1996 to 2024. Fifty-two studies (n=2,334) were reviewed and 23 (n=1,028) were analyzed quantitatively. Outcomes mainly included limb volume reduction, reliance on conservative treatment, improvement in infection rates, and improvement in the quality of life (QOL).ResultsLS-based treatments significantly reduce volume in both upper and lower limbs (91.08% and 92.03%). Standalone LS reduced limb volume by 99.74% but relied on continuous compression therapy. Combined approaches achieved slightly lower reductions (87.31%), but significantly decreased compression dependence, improved lymphatic function, and enhanced QOL. Furthermore, LS-based interventions were associated with a potential reduction in infection episodes, thereby providing long-term benefits.ConclusionLiposuction-based therapies effectively manage lymphedema by reducing limb volume and may reduce infections, while improving QOL. In addition, integrated approaches offer additional benefits by directly addressing lymphatic dysfunction and reducing reliance on compression therapy. Standardized methodologies and long-term studies are needed to refine the clinical guidelines and optimize outcomes. Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO, identifier CRD42024616130.